WORKSHOP FOTOGRAFI PERJALANAN UNTUK KONTEN INSTAGRAM - Bramantha, Octavianus (Jurnal Dewanagari, 2023)
SMK Negeri 57 Jakarta is the first public vocational high school in Indonesia which is engaged in tourism. Along with its development, since 2012 SMKN 57 Jakarta has added two expertise programs, namely Dance and Karawitan Arts, so that until now SMKN 57 has five Expertise Programs including: Tourism Business, Hospitality, Food Administration, Dance, Karawitan Arts. By looking at the potential and background of SMKN 57, the co-author of Mercu Buana University took the initiative to create a travel photography workshop for social media needs, especially Instagram. Because the development of this skill is felt to be able to develop the potential of one of the skills programs from SMKN 57.